Implementing of digital models in marketing, impact and perspectives - Tchanturia, Nino; Dalakishvili, Rusudan; Mushkudiani, Zurab; Gulua, Ekaterine (Journal of Eastern European and Central Asian Research (JEECAR), 2024)
The paper aims to study digital marketing models and their impact. Partly in response to the new digital age and partly due to the emergence of new marketing methods. Companies need to use different models to control their digital marketing plans. Due to the growing need for digital marketing models, they have investigated what models are in use today and whether it is possible to offer a new model to the market to make things easier for marketers. A new model was created based on one of the companies that use different digital tools. Marketers can learn helpful information from models when developing a digital marketing strategy, conducting an audit, or reviewing online communications. Company leaders must be aware that the marketing strategies they have adopted in the past year will not work under current conditions, which means they should be adapted to current trends.